Famished Souls Struggling for Food in George Orwell’s Down and Out in Paris and London - Raluca Ștefania PELIN (Cultural Intertexts)
Bread and margarine with wine, or “tea-and-two-slices”, presents a choice that triggers vast contemplations on poverty versus wealth and meaningful versus meaningless life. This paper aims to highlight how George Orwell’s Down and Out in Paris and London tackles the centrality of food and the people striving to obtain it. The purpose of this reading is to raise contemporary readers’ awareness of the inequality between the effort to procure food and the meagre outcomes, portrayed through a symphony of smells, a shocking juxtaposition of food abundance and scarcity, and a conflict of states needing interpretation. Orwell sets the two capitals in a mirroring progression where reflections magnify or diminish depending on people’s involvement in solving the constant dilemma of survival. While Paris offers the poor a chance to look for work, London reduces the struggle to mere begging for food, which is officially banned. The layered perspective brings the reader to a stark realization: a heavenly meal in a Parisian restaurant may have been prepared in “the hell of” a kitchen. In London, reality unfolds on a horizontal plane, where charities providing food deprive the poor of the chance to work for it. The contexts differ, but the props remain the same: filth, famine and an abundance of feelings.